2017
DOI: 10.1074/jbc.m116.769893
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular MicroRNA Signature of Human Helper T Cell Subsets in Health and Autoimmunity

Abstract: Upon T cell receptor stimulation, CD4 T helper (Th) lymphocytes release extracellular vesicles (EVs) containing microRNAs. However, no data are available on whether human CD4 T cell subsets release EVs containing different pattern of microRNAs. The present work aimed at filling this gap by assessing the microRNA content in EVs released upon T cell receptor stimulation of Th1, Th17, and T regulatory (Treg) cells. Our results indicate that EVs released by Treg cells are significantly different compared with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 63 publications
6
73
1
Order By: Relevance
“…Several investigators have shown different roles for miRNAs in haematopoiesis . A comprehensive miRNA profile of all hematopoietic cells, cell lineages and progenitors, miRNA from various subsets of CD4+ T cells, whereas the extracellular miRNA signature of T cells has been reported. On the other hand, miRNAs important for haematopoiesis and self‐renewal have also been reported .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several investigators have shown different roles for miRNAs in haematopoiesis . A comprehensive miRNA profile of all hematopoietic cells, cell lineages and progenitors, miRNA from various subsets of CD4+ T cells, whereas the extracellular miRNA signature of T cells has been reported. On the other hand, miRNAs important for haematopoiesis and self‐renewal have also been reported .…”
Section: Resultsmentioning
confidence: 99%
“…In order to understand which miRNA may be involved, we used the following approach. miRNA data reported to be either associated with CD4+ T cells, infected or uninfected with HIV were mined on PubMed. miRNA data reported to be associated with hematopoietic or myeloblastic differentiation were mined from PubMed. Databases were downloaded from the original references and their corresponding table number in the publication was noted (as indicated in Appendix ). To avoid duplications in between data sets reported by the various authors, Venn diagram analysis was carried out using GeneVenn for CD4+ T cell‐associated miRNA data and CD34+ differentiation‐associated miRNA data separately. Since GeneVenn can only analyse 3 sets of data simultaneously, the miRNA data sets associated with CD34+ were analysed in 2 batches and a compiled list of both batches together was used for final analysis. Finally, Venn analysis was carried out to determine miRNA common to both processes namely CD4+ T cell and CD34+ differentiation. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study simply correlates blood miRNA quantity with the knowledge that CD4 + T effector cells (in particular Th1 and Th17) are dramatically augmented in the skin of psoriasis patients, while the proportion of Treg cells is significantly increased upon anti‐TNF‐α therapies . The same study strongly suggests that the relative quantities of blood ‘proinflammatory’ versus ‘anti‐inflammatory’ extracellular miRNAs may be used as readout of the inflammatory state of autoimmune patients, before and after anti‐inflammatory drug treatment .…”
Section: Extracellular Vesicles: Novel Subcellular Players Of Metabolmentioning
confidence: 91%
“…Treg cells are traditionally known to directly suppress T cells by multiple mechanisms, including anti‐inflammatory cytokine release (IL‐10, TGF‐β, IL‐35) and high expression of IL‐2 receptor α chain, able to effectively compete for IL‐2 binding by Tconv cells. Similarly to other T‐cell subsets, Treg cells release EVs upon TCR stimulation, and these EVs contain a signature of miRNAs that differs from that released by Tconv cells in both mouse and human system, and not necessarily mirrors miRNA differential expression at the intracellular level . In particular, human Treg‐derived EVs are highly enriched with the anti‐inflammatory miR‐146a‐5p (Fig.…”
Section: Extracellular Vesicles: Novel Subcellular Players Of Metabolmentioning
confidence: 99%